Corona pandemic and its impact on contracts and transactions according to the theories of emergency conditions and force majeure - Abdul Whab Ali, Amerah (International Journal of Psychosocial Rehabilitation, 2020)
The research is based on the idea of ​​studying the jurisprudence of the effect caused by the emergence of a new virus on the whole world, according to the classification of developed countries at all levels, especially the level or the medical aspect. It is noticed that this virus caused problems in the public and private lives of people and their dealings. In fact, the study of the jurisprudence of the effect of this virus (Corona) on contracts and transactions is subject to two solid theories found in Islamic jurisprudence among the applicants and contemporaries, which are my theory (emergency circumstances and force majeure), therefore I reviewed the two theories quite well and showed the effects on the contracts in each of them and the means and methods of treatment , with mentioning contemporary applications on the impact of corona on contracts in Islamic law. It reached easy results, including :The scholars considered the Corona virus a pandemic or an effective excuse for completing the contracts, their economics and their budgets , and that the solutions to treat the effects of the Corona virus on the contracts are four solutions : either terminate the contract with an excuse, or place the pandemic, or reconcile the middle, or stop the execution of the contract until the emergency ceases . One of the most important recommendations: that the Iraqi judiciary should consider Kurna as an emergency circumstance in the contracts that happen in the context of exhaustion in its implementation, and a force majeure in contracts that happen to be an impossible milieu in their implementation. Not to consider it a force majeure only.